2014
DOI: 10.1136/bmjopen-2014-006175
|View full text |Cite
|
Sign up to set email alerts
|

High HIV seroprevalence, rectal STIs and risky sexual behaviour in men who have sex with men in Dar es Salaam and Tanga, Tanzania

Abstract: ObjectivesTo assess HIV and sexually transmitted infection (STI) prevalence and associated risk factors in men who have sex with men (MSM) in two cities in mainland Tanzania.MethodsWe conducted respondent-driven sampling of 300 MSM in Dar es Salaam and Tanga.ResultsIn Dar es Salaam, 172 (86%) men (median age 23, IQR 21–28) consented to HIV/STI testing, and 30.2% were HIV seropositive. Only five reported a previous positive HIV test: >90% were new HIV detections. 2.5% were syphilis-exposed and none hepatitis B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
76
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 27 publications
13
76
1
Order By: Relevance
“…The public health implication of this gendered sexual practice was substantively established by Beyrer et al who confirmed that the high probability of HIV transmission per act through the practice of receptive anal intercourse plays a central role in explaining the disproportionate disease burden in MSM [37]. It is not surprising that Ross et al later found that condomless receptive anal intercourse is significantly associated with sexually transmitted infections among MSM in Tanzania [38].…”
Section: Hiv Risk-taking Behavior In African Cultural Contexts: Africmentioning
confidence: 77%
See 1 more Smart Citation
“…The public health implication of this gendered sexual practice was substantively established by Beyrer et al who confirmed that the high probability of HIV transmission per act through the practice of receptive anal intercourse plays a central role in explaining the disproportionate disease burden in MSM [37]. It is not surprising that Ross et al later found that condomless receptive anal intercourse is significantly associated with sexually transmitted infections among MSM in Tanzania [38].…”
Section: Hiv Risk-taking Behavior In African Cultural Contexts: Africmentioning
confidence: 77%
“…Culturally relevant factors: These two items have also been used in MSM in Africa and found to be reliable [38].…”
Section: Level Of Experience Of Anti-gay Violencementioning
confidence: 99%
“…Syphilis and HIV co-infection presents a complex interaction. The increased incidence of HIV in homosexual and heterosexual individuals afflicted with STD, including syphilis is epidemiologically documented in numerous studies (Ross et al, 2014). HIV alters the course of syphilis as well as the response to treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Two hundred MSM from Dar es Salaam and 100 MSM from Tanga were recruited to participate using respondent-driven sampling (RDS) [21,23]. RDS, a snowball sampling method, employs 'seed' individuals to refer who they know; the latter then refer individuals they know using a predetermined number of coupons throughout the network [7].…”
Section: Methodsmentioning
confidence: 99%
“…Although childhood sexual abuse (CSA) has been implicated in HIV transmission among behaviorally heterosexual men, there are no published reports of the rate of CSA or its syndemic potential specifically among Tanzanian MSM [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%